Hubungan Pengetahuan Lingkungan Terhadap Sikap Siswa pada Pengelolaan Kebersihan di - Rahmi Muliana; Syarifah Farissi Hamama; Zamzami Zamzami (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The aims of this study was to investigate the relationship between students’ environmental knowledge and their behaviour in maintaining environmental cleanliness at school. This study was conducted at SMK Negeri 1 Mesjid Raya Aceh Besar with a total of 220 students from grade 8 and 9. The sample that used in this reseach were 69 students. Students’ knowledge were collected by using questioner, and question about students’ knowledge. The method which used in this research is descriptive design. Data analysis was performed with quantitative techniques, then processed using Product Moment correlation statistic. The result showed that the average value of students’ environmental knowledge at 78 in high category. On the other hand, students’ behaviour in environmental cleanlines at 58 in low category. Based on the result, it concluded that there were no relationship between student’s knowledge toward the management of cleanliness school environmental ( rhitung = 0.094 < rtabel = 0,235).